Estudio de adaptación de siete pastos y tres mezclas forrajeras con la utilización de lactofermento en el barrio san luis de Yacupungo parroquia Pastocalle cantón Latacunga provincia de Cotopaxi, 2018-2019. - Andrango Campues, Edgar Silverio (2020)
The present research was carried out in San Luis de Yacupungo Neighborhood, Pastocalle parish, Latacunga County, Cotopaxi Province, at an altitude of 3250 meters above sea level and coordinates X 07669966; Y 9923785.The main objective was to determine and achieve that the pastures have the adaptability to the ecotope of this place. Seven different grasses and three forage mixtures were used, with the application of enriched lactoferment. An experimental design in divided plots (A x B) was implemented, obtaining twenty treatments and three repetitions; the software INFOSTAT 2018 was used for the analysis of the following variables: percentage of germination, height of the plant, coverage and microbiological analysis of the soil. The pasture with the best agronomic behavior was the T5 treatment (Chicory) with a height of 37.77 cm at 43 days, and 44.14 cma at 50 days.Also the highest percentage of coverage (91.33%) at 57 days was reached by the T5 treatment (Chicory).With this information we can determine that the lactoferment worked in a representative way between the treatments and the soil fertility....